The Implementation of Al-Qur'an Memorization Program by Using Social Media in MA Sunan Giri Surabaya - Muhammad Ismail; Abdul Muhid (EDUCATIO : Journal of Education, 2020)
This study aims to describe the implementation of the Qur'an's tahfidz program by using social media at Senior Islamic High School of Sunan Giri Semampir Surabaya. The type of this research is a field research that the location is Senior Islamic High School of Sunan Giri as the executor of the Qur'an's memorizing extracurricular activities by looking for qualitative approach. The subject of this study involved the head of the school, the Trustees of the Qur’an memorizing program and participants of male and female students. Data collection using the method of observation, interviews and documentation. This Study uses the analytical method of Miles Huberman model with three steps, namely data reduction, data presentation, and drawing conclusions. The result of this research is: First, the Tahfidz Program in MA Sunan Giri Surabaya is a new program with memorization of 5 juz for students who stay in dormitory and 2 juz for non-boarding students. Second, the process of implementing memorization through social media, with 3 stages, namely: 1) Reading together verses to be memorized, 2) Memorizing students at their homes with the assistance of parents, 3) students' memorizes to the teacher through video calls. Third, the implementation of the Qur’an’s memorizing program went well as expected as the program is usually in the school